Training needs of newly integrated schools and guidance counselors for developing counseling skills - LAAROUSSI, Djamila; BEDOUI, Aicha (Social Sciences Journal)
The study aims to identify the level of training needs of newly integrated school and vocational guidance counselors for the development of counseling skills. To achieve the objectives of the study, a questionnaire was prepared, consisting of 49 items distributed across four skills, and administered to a sample of 57 newly integrated school and vocational counselors. After verifying the validity and reliability of the questionnaire, the results revealed that the level of training needs was high across all skills. The findings also indicated that counselors need training in the following order: case management and follow-up skills, program development skills, counseling relationship-building skills, and diagnostic skills